2008
DOI: 10.1002/ptr.2480
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the antibacterial activity of propolis from different geographical and climatic zones

Abstract: Propolis is a natural substance produced by honeybees upon collection and transformation of resins and exudates from plants. Comparative studies on propolis collected from a wide range of countries are crucial for linking its provenance to antibacterial activity and thus ensuring that the beneficial properties of propolis are used more efficiently by the general public. This study reports the in vitro screening of ethanol extracts of propolis (n = 40), collected from a wide range of countries within the tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 74 publications
6
96
3
6
Order By: Relevance
“…In this study, the ethanolic extract of propolis obtained from Tabora displayed activity on almost all tested microorganisms (MIC 0.42 -1.67 mg/ml) with only Pseudomonas aeruginosa being resistant to this extract. This is in agreement with a previous study on Tanzanian propolis; although in that study the specific area where propolis was collected was not indicated (Seidel et al, 2008). On the other hand the ethanolic extract of propolis from Iringa was able to inhibit growth of five out of nine microorganisms tested, with MICs ranging from 1.67 to 6.67mg/ml.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the ethanolic extract of propolis obtained from Tabora displayed activity on almost all tested microorganisms (MIC 0.42 -1.67 mg/ml) with only Pseudomonas aeruginosa being resistant to this extract. This is in agreement with a previous study on Tanzanian propolis; although in that study the specific area where propolis was collected was not indicated (Seidel et al, 2008). On the other hand the ethanolic extract of propolis from Iringa was able to inhibit growth of five out of nine microorganisms tested, with MICs ranging from 1.67 to 6.67mg/ml.…”
Section: Resultssupporting
confidence: 92%
“…This extract was not active against S. aureus, S. typhi, P. aeruginosa and S. faecalis at the tested concentrations. The observed MICs for both samples were several times higher when compared to a previous report on Tanzanian propolis (Seidel et al, 2008), where MICs ranged from 15.62 to 250 mg/l for Gram +ve bacteria. The MICs observed in this study were somehow similar to those reported in another study on propolis from Italy (Scazzocchio et al, 2006).…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Compounds 1-5 were from Sigma-Aldrich; compound 6 was isolated from propolis (Raghukumar et al, 2010) and 7-9 were purified from plants (Gordien et al, 2009;Shilpi et al, 2010). These compounds were selected because they had previously demonstrated some antimicrobial activity (Seidel et al, 2008;Shilpi et al, 2010) and/or because they were part of our laboratory database of authentic standards available in sufficient amounts for biological screening. All compounds were dissolved in DMSO (2 mg ml 21 ) to prepare stock solutions and diluted with cellculture medium to 18 mg ml 21 (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…A broth microdilution method was used to determine MICs, as described previously (Seidel et al, 2008).…”
Section: Methodsmentioning
confidence: 99%